Molecular phylogenetic relationships reveal taxonomic and biogeographic clades in Dianella (flax lilies; Asphodelaceae, Hemerocallidoideae). Issue 3 (3rd April 2019) - Muscat, Karen M.; Ladiges, Pauline Y.; Bayly, Michael J.
Abstract : A phylogeny of Dianella is presented based on Bayesian and maximum parsimony analyses of a combined molecular data set using three chloroplast markers ( trn Q UUG –5' rps 16, 3' rps 16–5' trn K (UUU) and rpl 14– rps 8– inf A– rpl 36) and two nuclear markers (ITS and ETS). Accessions included most Dianella species, including all species from Australia, the centre of diversity for the genus, and related outgroup genera Eccremis, Stypandra, Thelionema and Herpolirion. The phylogeny showed Stypandra sister to Herpolirion + Thelionema, and confirmed the monophyly of Dianella. Within Dianella, a number of clades were resolved that revealed biogeographic relationships. Accessions from south-western Australia (extending into South Australia) formed the earliest diverging clade, followed by D. serrulata from New Guinea, sister to all other clades of Dianella from Australia and other regions. Tropical North Queensland species, including the D. pavopennacea complex, were related to a clade of accessions from New Caledonia and the Hawaiian Islands in the Pacific, and a clade that included samples of D. carolinensis (Caroline Islands) and the widespread D. ensifolia from South-East Asia and across the Indian Ocean to Mauritius and Madagascar. However, D. ensifolia is not monophyletic, with accessions from Japan and Taiwan related to a clade of Queensland samples that are part of the D. revoluta complex. Three New Zealand species (diploid, 2n = 16) were found to be related to Norfolk Island D. intermedia (type locality; octoploid, 2n = 64). In contrast ' D. intermedia ' from Lord Howe Island was resolved as sister to the eastern Australian D. caerulea complex. The phylogenetic results indicate the need for taxonomic revision, particularly revision of the species 'complexes' D. longifolia and D. caerulea in Australia, and recognition of more than one species within D. ensifolia and within D. sandwicensis on the Hawaiian Islands.